Retrospective investigation of enteric illnesses in pet animals - Mohamed O Ahmed; Hiam R Elnageh; Abojala Elhashmi Ammar; Emadeddin Abdulkarim; Ali Alareid; Murad A Hiblu; Yousef M Abouzeed (Intelektual Pustaka Media Utama, 2019)
Recording and analysis of data are key elements to understand the epidemiology of various infectious and zoonotic diseases such as enteric pathogens and conditions. In this study, the clinical records of Alhelal Alazraq veterinary clinic in Tripoli were investigated for enteric diseases and illnesses in cats and dogs during the period of 2010–2015. The diagnostic and therapeutic guidelines within the Libyan veterinary system were also assessed and discussed based on the retrieved information and records. A total of 859 cases representing 528 (61%) from cats and 331 (39%) from dogs were retrieved and analysed using descriptive analysis. The cases were originated from five major areas from the center of Tripoli and the surrounding areas. Of these, 835/859 (97%) cases adopted antimicrobial based therapies and administered various antibiotic classes mainly and respectively using penicillin (652; 78%) and trimethoprim-sulfamethoxazole (229; 27%). The current study is the first retrospective investigation that analysed clinical and medical information from a major veterinary clinic in Libya. Diagnostic and therapeutic guidelines in the veterinary settings in Libya should be carefully reviewed and addressed. Retrospective studies and research programmes that monitor and investigate the occurrences of zoonotic and emerging pathogens particularly in relation to antimicrobial resistance are warranted in the Libyan health and medical systems